(4a^2+b^2)^2-(4ab)^2 因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 15:32:26
(4a^2+b^2)^2-(4ab)^2因式分解(4a^2+b^2)^2-(4ab)^2因式分解(4a^2+b^2)^2-(4ab)^2因式分解原式=(4a²+b²+4ab)(4a
(4a^2+b^2)^2-(4ab)^2 因式分解
(4a^2+b^2)^2-(4ab)^2 因式分解
(4a^2+b^2)^2-(4ab)^2 因式分解
原式=(4a²+b²+4ab)(4a²+b²-4ab)
=(2a+b)²(2a-b)²
(4a^2+b^2)^2-(4ab)^2
=(4a^2+b^2-4ab)(4a^2+b^2+4ab)
=(2a-b)^2(2a+b)^2
(4a^2+b^2)^2-(4ab)^2
=(4a^2+b^2-4ab)(4a^2+b^2+4ab)
=(2a-b)^2(2a+b)^2
你好,解答如下:
(4a^2+b^2)^2-(4ab)^2
=(4a² + b² - 4ab)(4a² + b² + 4ab)
=(2a - b)²(2a + b)²
(4a^2-b^2)^2
(4a^2+b^2)^2-(4ab)^2=16a^4+b^4+8a^2b^2-16a^2b^2=16a^4+b^4-8a^2b^2
=(4a^2-b^2)^2=(2a+b)^2(2a-b)^2
(4a^2-b^2)^2
原式=(4a²+b²+4ab)(4a²+b²-4ab)
=(2a+b)²(2a-b)²
a^2b-ab+2ab^2-5a^b-4ab+3ab^2化简快
2a²b(a-b)+ab(a-b)²+4ab²(a-b)
4ab/b^2(a-b)=
a-b/a^2+ab / ab-a^2/a^2b^2-b^4快
5ab^2-{2a^b-[3ab^2-(4ab^2-2a^2b)]}
计算:[(a+b)^2-4ab][(a-b)^2+4ab]-(a^2-b^2)^2
1/4a^2b^2{3ab(a+b)-5a(ab-b^2)}=?
a>0,b>0,2a+b+ab=4,ab,2a+b最值
a+b/2ab
2AB/A+B
a+b/2ab
计算(a^2-4b^2)/(a^2-ab)*(a-b)/(a^2-2ab)
4a^2b-4ab^2-2ab 因式分解
(a^2b^2+ab)^2-(ab+4)^2因式分解
因式分解:2a^2b-4ab^2+8ab
证明(a^2+ab+b^2)^2+4ab(a+b)^2=(a^2+3ab+b^2)
证明(a^2+ab+b^2)^2+4ab(a+b)^2=(a^2+3ab+b^2)
-3/4ab+2/3a^2b+ab-a^2b-1/2ab-5/3a^2b